Impact of exercise-based cardiac rehabilitation on cardiopulmonary function and prognosis in ST elevation myocardial infarction after PCI patients in extremely cold regions - Shenglong Hou; Li Liu; Jing Yao; Qi Zhao; Wei Feng; Qingqing Liu; Mou Zou; Ruoxi Zhang; Hongtao Yin; Huimin Xian (BMC Cardiovascular Disorders)
Abstract Purpose To evaluate the impact of exercise-based cardiac rehabilitation (CR) on the cardiopulmonary function and prognosis in post-percutaneous coronary intervention (PCI) patients with ST elevation myocardial infarction (STEMI) in extremely cold regions of China. Methods This retrospective study included 2,162 patients diagnosed with STEMI who were treated at five medical centers in extremely cold regions of China, between January 2020 and December 2023. All included patients underwent emergency coronary angiography and PCI. Based on whether they received exercise-based CR, patients were divided into a CR group and a non-CR group. To adjust for variations in initial risk factors and baseline characteristics between patients who underwent CR or not, we employed the propensity score matching. Each patient was matched in a 1:1 ratio with replacement. Patients who either participated in CR or did not, but could not be adequately matched, were excluded from the study population. Patient information between the two groups was systematically compared in hospital and at follow-up. Results The rate of heart failure, re-hospitalization, and ventricular arrhythmia in CR group was significantly lower than that in non-CR group. The left ventricular ejection fraction (LVEF) measured by echocardiography in CR group were significantly higher than those in non-CR group. The cardiopulmonary test indicators for patients in CR group showed significant improvement over one year, including Power, HR, VCO₂, VO₂, VE, VD/VT, PetCO₂, CHO, CO, and SV, all with statistical significance. Multivariate COX regression analysis showed that CR was independently associated with heart failure in follow up. Conclusion Exercise-based CR effectively improves the recovery of cardiac function and prognosis in post-PCI patients with STEMI in extremely cold regions of China. Graphical Abstract